2023
DOI: 10.3389/fpubh.2023.1133657
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and associated factors among people living with HIV/AIDS in Sichuan, China: A cross-sectional study

Abstract: PurposeThis study aimed to explore health-related quality of life (HRQoL) and its associated factors among people living with HIV/AIDS (PLWH) in Sichuan, China.MethodsA total of 401 PLWH were recruited from the city of Panzhihua between August 2018 and January 2019. Demographic characteristics and disease-related data were collected by self-administered questionnaires and medical system records. Health-related quality of life (HRQoL) was measured by the medical outcome study HIV health survey (MOS-HIV), which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Indeed, it has been shown that PLWHA often have a lower HRQOL than healthy people [3]. Many factors have been reported to affect the HRQOL of PLWHA, such as age, educational status, social support, economic status, stigma, CD4 lymphocyte count, antiretroviral therapy, and body mass index [4][5][6][7][8][9]. Intervention measures target these factors will contribute to improve the HRQOL for PLWHA.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been shown that PLWHA often have a lower HRQOL than healthy people [3]. Many factors have been reported to affect the HRQOL of PLWHA, such as age, educational status, social support, economic status, stigma, CD4 lymphocyte count, antiretroviral therapy, and body mass index [4][5][6][7][8][9]. Intervention measures target these factors will contribute to improve the HRQOL for PLWHA.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of life experienced by PLHIV in Sinchuan Province is comparatively substandard. Several factors have been found to have a good correlation with quality of life, including age, education level, methadone use, CD4, lymphocyte count, number of symptoms, and body mass index [26]. A study with minimal variations was carried out in Zhejiang Province.…”
Section: Introductionmentioning
confidence: 99%
“…Various patient-reported outcome (PRO) measures could be utilized to support HIV management by capturing patients' ART experience accurately, evaluating and differentiating treatment strategy and predict clinical outcomes [5]. Previous studies have evaluated and found the low HRQoL and associated factors in HIV patients [6][7][8][9]. Nevertheless, majority of the studies were conducted before BIC/FTC/TAF or DTG/3TC included in NRDL and have no restriction on the regimen received.…”
Section: Introductionmentioning
confidence: 99%